2022
DOI: 10.1038/s41467-022-32244-w
|View full text |Cite
|
Sign up to set email alerts
|

Land use change and carbon emissions of a transformation to timber cities

Abstract: Using engineered wood for construction has been discussed for climate change mitigation. It remains unclear where and in which way the additional demand for wooden construction material shall be fulfilled. Here we assess the global and regional impacts of increased demand for engineered wood on land use and associated CO2 emissions until 2100 using an open-source land system model. We show that if 90% of the new urban population would be housed in newly built urban mid-rise buildings with wooden constructions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(65 citation statements)
references
References 74 publications
0
65
0
Order By: Relevance
“…A widely promoted solution to tackle embodied emissions of materials, advocated by researchers and policymakers, is for timber to replace concrete and steel in construction (Churkina et al 2020;Mishra et al 2022). Yet, a building constructed from timber alone just transfers carbon from one carbon pool (the forest) to another carbon pool (the built environment) (Arehart et al 2021).…”
Section: Global Northmentioning
confidence: 99%
“…A widely promoted solution to tackle embodied emissions of materials, advocated by researchers and policymakers, is for timber to replace concrete and steel in construction (Churkina et al 2020;Mishra et al 2022). Yet, a building constructed from timber alone just transfers carbon from one carbon pool (the forest) to another carbon pool (the built environment) (Arehart et al 2021).…”
Section: Global Northmentioning
confidence: 99%
“…Thus, with the urbanization process, we will see a rise in wood products used for home applications and constructions. Mishra et al (2022) found that if 90% of the new urban people build their houses with wooden materials, 106 Pg of CO 2 will be sequestered by 2100. Skjerstad et al (2021) suggested that the sawn wood consumption will continue increasing in line with the future economic growth.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…The substitution option exhibits an additional benefit alongside lower embodied emissions, as wooden construction materials (WCMs) act as long-term carbon storages. The use of these materials has been suggested as a strategy to decrease the consumption of more carbon intensive materials [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[21,22]), and ultimately on a global level (e.g. [10,23]). These studies present a clear trend of lower embodied emissions when using WCM.…”
Section: Introductionmentioning
confidence: 99%